Roux-en-Y Gastric Bypass and Sleeve Gastrectomy as Revisional Bariatric Procedures after Adjustable Gastric Banding: a retrospective cohort study - Luís Pedro Pereira Lindeza (2021)
Introduction: Obesity is a worldwide pandemic and a well-known risk factor for several diseases. Bariatric surgery is more effective than conventional medical treatments regarding weight loss and resolution of comorbidities. The laparoscopic AGB was a very popular bariatric procedure, but its use has declined in recent years. Nowadays, the most frequent bariatric surgeries are RYGB and SG. The frequency of revisional bariatric surgery is increasing worldwide, even though results concerning their outcomes and safety are not yet very established. The aim of our study was to compare short-term outcomes of primary (pRYGB and pSG) vs. revisional bariatric surgeries (rRYGB and rSG), and between revisional interventions themselves on weight loss outcomes, surgical complications, and resolution of comorbidities. Methods: This is a retrospective cohort study with 494 patients with obesity submitted to bariatric surgery in 2019 in a single tertiary hospital, 93 (18.8%) of them were patients undergoing a revisional bariatric surgery after a failed AGB. Results: Patients submitted to pRYGB lost more weight than those who underwent rRYGB. (%EWL at 12 months 87.50 [IQR 78.08 -101.06] vs. 82.64 [IQR 68.01 - 93.62]; p=0,004). %EWL values 6 months and 12 months postoperatively were also statistically different between the pSG and rSG groups, with the patients submitted to pSG having more desirable outcomes. Comparing both revisional procedures, the patients who undertook rRYGB lost more weight than those with rSG (%EWL at 12 months 82.64 [IQR 68.01 - 93.62] vs 69.01 [IQR 51.20 - 74.82], p<0,001). Concerning surgical complications, no differences in morbidity and mortality were found. Regarding the resolution of obesity-related comorbidities, 54.2% of the patients in the pRYGB group vs. 25.0% in the rRYGB group had a resolution of diabetes (p=0.038). Also, 41.7% of the patients who underwent a rRYGB in comparison with 0 patients from the rSG group had a resolution of dyslipidaemia (p=0.035). Patients submitted to pSG had a significant resolution of dyslipidaemia when compared to patients submitted to rSG (68.6% vs 0.0%; p=0.001). Conclusion: Revisional bariatric surgery is an effective and safe option to treat obesity and related comorbidities. Our results showed worst weight loss outcomes of revisional compared to primary RYGB and SG. RYGB has better weight loss outcomes than SG when they are both used as conversion procedures following failed AGB. Further clinical studies, preferably with a prospective design and longer follow-up, are needed to better understand the role of revisional bariatric surgery.